Delito de estelionato frente a la venta de bienes ajenos como propios en el distrito judicial de Loreto Iquitos 2024 - Rengifo Vasquez de Luzinsky, Ornella Fiorella (2026)
The objective of this study was to determine the relational link between the crime of estelionato and the sale of another's property as one's own in the judicial district of Loreto. It should be mentioned that the crime of estelionato in the form of selling another's property is not configured solely by the sale of a property that does not belong to the seller. For the crime to exist, it is necessary that the objective and subjective elements of the crime are met, mainly an appropriate deception that causes financial harm to the buyer. Therefore, the sale of another's property is legal when there is no deception or fraud, and in that case, estelionato is not configured. The methodology used was a quantitative, non-experimental design. The study population was 30 justice administrators (Judges, Prosecutors, and Lawyers), the technique used was the survey, and the instrument was the questionnaire. The most important results show that the reliability coefficient for variable 1: Crime of Estelionato is 0.925 and variable 2: Sale of Another's Property as One's Own is 0.951, indicating high reliability in the processed data. The Pearson correlation value is 0.994**, which indicates a strong correlation value and a bilateral significance of 0.00, which is very significant. It is concluded that this could indicate efficiency and consistency in judicial practices.